Analisis Faktor-Faktor yang Mempengaruhi Audit Delay pada Perusahaan Manufaktur yang Terdaftar di BEI - Ustman, Ustman; Agustina, Mellyana Norma (Journal of Economics and Management Scienties, 2025)
The purpose of this research is to analyze the effect of audit opinion, company size, profitability, solvency and quality of auditors on the accuracy of the delivery of financial reports. This research is a quantitative study with five independent variables and one dependent variable. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2019-2021 period. The research sample consisted of 150 samples obtained by purposive sampling technique and using multiple regression analysis techniques which began with the classical assumption test.The results showed that partially audit opinion, company size, profitability and solvency variables had no effect on audit delay. On the other hand, the auditor quality variable has an effect on audit delay. Simultaneously audit opinion, firm size, profitability, solvency and quality of auditors affect audit delay